Analysis Of Insider Ownership, Debt Policy And Dividend Policy As Intervening Variables On The Firm Value Of Companies In The Mining Sector Listed On The Indonesia Stock Exchange In 2019-2023 - Pramesti, Tia; Safitri, Maria; Setyahuni, Suhita Whini; Oktavia, Vicky (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study focuses on Indonesia Stock Exchange (IDX) companies in the mining sector for the period 2019-2023 which aims to analyze the role of managerial ownership on firm value, the role of debt policy on firm value, and the role of dividend policy as a mediator on managerial ownership and debt policy on firm value. This study uses quantitative methods and data analysis techniques for this study using SmartPLS-SEM. The results of the study found that managerial ownership (X1), debt policy (X2), dividend policy (Z) have a significant effect on firm value (Y), while the role of managerial ownership (X1) and debt policy (X2) through dividend policy (Z) as a mediator has an insignificant and significant effect.